Clinical and Laboratory Evaluations of Patients Diagnosed as Having Multisystem Inflammatory Syndrome Associated with Coronavirus Disease 2019 in Children: A Single Center Experience from Konya - Gençeli, Mustafa; Akcan, Özge Metin; Erdoğan, Kübra Nur; Kiliç, Ahmet Osman; Yazar, Abdullah; Akin, Fatih; Güneş, Muhammed; Şap, Fatih; Oflaz, Mehmet Burhan; Feyzioğlu, Bahadır (Journal of Pediatric Infectious Diseases, 2022)
Objective Multisystem inflammatory syndrome in children (MIS-C), characterized by fever, inflammation, and multiorgan dysfunction, was newly defined after severe acute respiratory syndrome coronavirus 2 infection. The clinical spectrum of MIS-C can be classified as mild, moderate, and severe. We aimed to evaluate demographics, clinical presentations, laboratory findings, and treatment modalities of patients with MIS-C according to clinical severity.Methods We performed a retrospective study of patients who were diagnosed as having MIS-C between September 2020 and October 2021 in the Necmettin Erbakan University Meram Faculty of Medicine, Türkiye.Results A total of 48 patients (24 females and 24 males) with a median age at diagnosis of 10.3 years (range: 42 months–17 years) were enrolled, the most common clinical severity of MIS-C was moderate. The common presentations of patients were fever (97%), nonpurulent conjunctivitis (89.6%), rashes (81.3%), fatigue (81.3%), strawberry tongue (79.2%), and myalgia (68.8%). The most common laboratory findings were lymphopenia (81.2%), thrombocytopenia (54.1%), elevated D-dimer levels (89.5%), C-reactive protein (CRP; 100%), procalcitonin (97%), erythrocyte sedimentation rate (87.5%), ferritin (95.8%), interleukin 6 (IL-6) (86.1%), and probrain natriuretic peptide (pro-BNP) (97%). High levels of CRP, procalcitonin, pro-BNP, and urea were associated with the severity of MIS-C (p < 0.05). Fifteen of the patients were found to have pulmonary involvement. Ascites were the most common finding on abdominal ultrasonography (11 patients) and were not seen in a mild form of the disease. During the study period, two patients died.Conclusion It is important to make patient-based decisions and apply a stepwise approach in treating patients with MIS-C due to the increased risk of complications and mortality.
Keywords: Multisystem inflammatory syndrome in children; COVID-19; clinical and laboratory findings